Informed consent at stake? Language barriers in medical interactions with immigrant anaesthetists: a conversation analytical study - Damaris Borowski; Uwe Koreik; Udo Ohm; Claudia Riemer; Niels Rahe-Meyer (BMC Health Services Research, 2019)
Abstract Background Language barriers in doctor-patient interactions are still an understudied phenomenon. This is particularly true concerning interactions with immigrant physicians who are learners of the patient’s language; there is a lack of research even though labour migration is increasing internationally. This conversation analytical study focusses on language errors in one specific type of doctor-patient interaction, namely pre-anaesthesia evaluations with immigrant anaesthetists. Methods The study combines the research field of language acquisition with that of medical interaction. It is a qualitative study with an ethnomethodological framework which addresses the following research question: How do language errors, produced by immigrant anaesthetists, impact pre-anaesthesia evaluations? The primary data comes from naturally occurring pre-anaesthesia evaluations carried out by immigrant anaesthetists. The analysis method is a combination of conversation and error analysis. Results The study shows that the anaesthetists produced a considerable number of unintelligible utterances, due to various language errors. Despite the lack of understanding, hardly any negotiation of meaning occurred and both sides (anaesthetists and patients) claimed to be satisfied. Conclusions The findings appear to be contradictory. An explanation for this can be found in the effect of the roles and scripts that are given in pre-anaesthesia evaluations. Since no negotiation of meaning is initiated during the interactions, the anaesthetists’ insufficient language competence leads to a considerable impairment of informed consent, which is the main goal of the pre-anaesthesia evaluations. Based on these findings, the study reveals an urgent need for action regarding immigrant anaesthetists’ language skills.